Distinct transcriptomic responses of Caenorhabditis elegans to pristine and sulfidized silver nanoparticles. (June 2016) - Starnes, Daniel L.; Lichtenberg, Stuart S.; Unrine, Jason M.; Starnes, Catherine P.; Oostveen, Emily K.; Lowry, Gregory V.; Bertsch, Paul M.; Tsyusko, Olga V.
Abstract: Manufactured nanoparticles (MNP) rapidly undergo aging processes once released from products. Silver sulfide (Ag2 S) is the major transformation product formed during the wastewater treatment process for Ag-MNP. We examined toxicogenomic responses of pristine Ag-MNP, sulfidized Ag-MNP (sAg-MNP), and AgNO3 to a model soil organism, Caenorhabditis elegans . Transcriptomic profiling of nematodes which were exposed at the EC30 for reproduction for AgNO3, Ag-MNP, and sAg-MNP resulted in 571 differentially expressed genes. We independently verified expression of 4 genes ( numr-1, rol-8, col-158, and grl-20 ) using qRT-PCR. Only 11% of differentially expressed genes were common among the three treatments. Gene ontology enrichment analysis also revealed that Ag-MNP and sAg-MNP had distinct toxicity mechanisms and did not share any of the biological processes. The processes most affected by Ag-MNP relate to metabolism, while those processes most affected by sAg-MNP relate to molting and the cuticle, and the most impacted processes for AgNO3 exposed nematodes was stress related. Additionally, as observed from qRT-PCR and mutant experiments, the responses to sAg-MNP were distinct from AgNO3 while some of the effects of pristine MNP were similar to AgNO3, suggesting that effects from Ag-MNP is partially due to dissolved silver ions. Graphical abstract: Highlights: Some effects of pristine silver nanoparticles can be linked to Ag + . Sulfidized silver nanoparticles have effects independent of Ag + . Sulfidized silver nanoparticle responses suggest cuticle damage. Distinct toxicity pathways indicated for all three treatments. Abstract : The toxicity of fully sulfidized Ag nanoparticles is not due to release of Ag ions.